Child Resource Centres as Catalysts for Academic Achievement and Social Inclusion in Tribal Education (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Determining how Child Resource Centres (CRCs) can improve access to education and help achieve educational goals while promoting social inclusion and integration in education literature, focussing on CRCs social, family, and infrastructure barriers to children's educational outcomes. Tribal communities historically with large under-resourced families face challenges such as low educational attainment and early marriage, responsibilities and drop-out rates. This particularly disadvantages girls. This research covered 360 tribal parents living in Dahanu, Vikramgad, Jawahar, Mokhada, and Talasari, collecting and analysing social surveys under age, family structure, social family classification, dwelling, and basic social and personality traits and household decision-maker structure. Parents were generally young, families were predominantly nuclear, many owned Aadhars and ration cards, and most families lacked piped water and underground drainage. The CRCs offer social educational and social development aimed at the strategic goals of full inclusion and integration of educational resources to promote social inclusion and integration of education to foster development of the child in a gender sensitive and socio-psychological perspective. CRCs assist in closing economic and cultural barriers while providing social support to families in the community around the CRCs to promote equal educational opportunities. These centres can transform the lives of tribal children located in the remote regions of the country. They improve academic progress, promote social involvement and help in the overall uplifting of tribal children.